SUITABILITY OF DIGITAL JOMBANG FOLKLORE FOR STUDENT INTERACTION - Aang Fatihul Islam; Lusia Septiana Riduwan (LPPM Universitas PGRI Jombang, 2025)
This study examines the suitability of Jombang digital folktales in enhancing English language learning, with a particular focus on narrative texts. The objective is to evaluate how incorporating local cultural elements through digital Jombang folklore suitability student interaction during the teaching and learning process. The research employed a quantitative quasi-experimental approach, collecting data through pre and post questionnaires completed by students following an introduction to Jombang folklore. Statistical analysis indicated that initial differences among students did not significantly impact the post-test results, suggesting that the intervention had a more substantial influence. This finding supports previous research that highlights the value of integrating folklore in English education to boost student interest and cultural awareness. The quantitative method utilized in this study involved questionnaires administered after students were exposed to Jombang folklore. Results demonstrated that digital storytelling of Jombang folktales actively suitability students in learning activities, as evidenced by the improvement in post-questionnaire scores compared to pre-questionnaire scores. Ultimately, this research aims to contribute positively to the creation of engaging and meaningful learning resources for students, while also enhancing their understanding of Indonesian culture.